2018
DOI: 10.1016/j.cpr.2018.01.008
|View full text |Cite
|
Sign up to set email alerts
|

eHealth interventions for family carers of people with long term illness: A promising approach?

Abstract: Family carers of people who have long term illness often experience physical and mental health morbidities, and burden. While there is good evidence to suggest that carers benefit from psychosocial interventions, these have primarily been delivered via face-to-face individual or group-formats. eHealth interventions offer a novel, accessible and self-paced approach to care delivery. Whether these are effective for carers' wellbeing has been little explored. This paper reports the first comprehensive systematic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(139 citation statements)
references
References 117 publications
3
136
0
Order By: Relevance
“…9 Mental health services are often designed to be family and friends orientated and digital interventions could play an important role by providing support digitally where practical issues may impede access to conventional psychosocial interventions. 10,11 To date trials have shown that online psychoeducation is useful and acceptable to relatives of those with bipolar disorder 12 and schizophrenia. 9 Despite their potential, there have been widespread difficulties in integrating and implementing digital interventions into real-world clinical settings, an indication of the evidence-practice gap.…”
Section: Investment and Interest In Digital Interventions Ismentioning
confidence: 99%
“…9 Mental health services are often designed to be family and friends orientated and digital interventions could play an important role by providing support digitally where practical issues may impede access to conventional psychosocial interventions. 10,11 To date trials have shown that online psychoeducation is useful and acceptable to relatives of those with bipolar disorder 12 and schizophrenia. 9 Despite their potential, there have been widespread difficulties in integrating and implementing digital interventions into real-world clinical settings, an indication of the evidence-practice gap.…”
Section: Investment and Interest In Digital Interventions Ismentioning
confidence: 99%
“…Each criterion is scored from 0 to 2 (2 = criterion met; 1 = unclear; 0 = criterion not met) [44]. This measure was applied in the previous eHealth review [45].…”
Section: Study Quality Assessmentmentioning
confidence: 99%
“…the elderly (Bujnowska-Fedak & Pirogowicz, 2014) caretakers (e.g. Sin et al, 2018) or people with certain diseases (e.g. Haberlin et al, 2018).…”
Section: Ehealth Implementation Adoption and Usementioning
confidence: 99%